Laser pyrolyzed organosilazane-based Al/ZrO2 composite coating on stainless steel: Resulting microstructure and mechanical properties - Horcher, Alexander; Tangermann-Gerk, Katja; Krenkel, Walter; Schmidt, Michael; Bordia, Rajendra K.; Motz, Guenter (International Journal of Applied Ceramic Technology, 2021)
Protective ceramic-based coatings are frequently the most suitable solutions for problems like corrosion and wear. It has been shown that the precursor technology is suitable for the preparation of ceramic coatings by pyrolysis in a furnace. However, the required high temperature for the preparation of the ceramic coatings limits this approach to high temperature-resistant substrates. A very innovative approach to overcome this restriction is the use of laser radiation as a thermal source for the pyrolysis of the preceramic polymer. In this paper, we report on a coating system, for steel substrates, consisting of a polysilazane (Durazane 2250) bond coat and a hard and dense top-coat composed of an organosilazane (Durazane 1800) with tetragonal ZrO2 particles and aluminum flakes as fillers pyrolyzed using Nd:YVO4 laser. The aluminum fillers led to a significant increase in absorption of the laser energy leading to the formation of a dense coating with a thickness up to 20 mu m and a mainly cellular/columnar-dendritic microstructure. The microstructure, mechanical, and tribological behaviors of these composite coatings are reported and compared to those of laser pyrolyzed glass/ZrO2-filled polysilazane-based coatings reported in the literature.
CRIS-Team WoS Importer:2021-10-15